PENGARUH TEKNIK MASSAGE COUNTER PRESSURE TERHADAP PENGURANGAN RASA NYERI PERSALINAN KALA I - Kristin - Natalia (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2020)
Labor pain is a physiological condition that is generally experienced by almost all women who give birth. Pain comes from uterine contractions and cervical dilation. With the increasing frequency of uterine contractions, the pain you feel will get stronger. This study aims to determine the Effect of Counter Pressure Massage Techniques on the Reduction of Pain in Stage I Labor at Kardi Lestari Primary Clinic. This study uses a quantitative analytical method with a Quasy-Experimental research design with the One Group Pretest-Posttest approach. Data collection techniques using observation sheets. This Counter Pressure Massage technique is performed for 20 minutes / hour during contraction. The population in this study were 8 maternity mothers. The sampling technique used was purposive sampling method. Data analysis using the Wilcoxon Test. The results of this study showed that giving the massage counter pressure technique to the lumbar part of the mother at the Kardi Lestari Pratama Clinic can reduce labor pain from mothers who experience moderate pain to mild pain and mothers who experience severe pain to moderate pain with p value = 0.007 (p. <0.05). It can be concluded that there is a significant influence with the application of the Counter-Pressure Massage Technique on the reduction of pain in Kala I labor. the technique at the time of delivery.